Consent to Data Linkage in LSAC - Dinusha Bandara; Michelle Silbert; Galina Daraganova (International Journal of Population Data Science, 2020)
Introduction Linking the existing longitudinal data assets with administrative datasets provide the opportunity to transform longitudinal data into valuable assets to inform research and policy development.